(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
The God has blessed the female with most valuable gift of motherhood mother is also called as “Janani’’ who give birth to child. A woman hood is never considered complete without achievement of motherhood. Infertility is a burning issue because today’s changing lifestyle and stress increases metabolic and hormonal disturbance as a result diabetes, PCOS, infertility. Our focus is, if a woman having normal anatomy of pelvic organ than she should conceive by natural way by Ayurvedic treatment because more side effect of ovulation induction and hormonal therapy. In Ayurveda Bandhyatva (infertility) mainly occurs vitiation of Vata and Kapha Dosha, in some case Pitta may involve. Fertility also depends on mental condition of couple as Charak says sound mind couple gets conceived easily. In this patient had also metabolic disturbance and stress, and ineffective endometrial receptiveness, so we choose Ashwagandha (Withania somnifera) as a anti-stress and normalize Vata and Kapha and Shatavari (Asparagus racemosa) for endometrial tonicity and Sthanik (endometrial) Pitta Shaman and Chandraprabha for Apana Vata (pelvic) disorder, balancing Tridosha and for Dhatvagni Deepan (better metabolism).